Surgical management of a periapical cyst injury. Case Report - Medina Mosqueira, María (2010)
Diagnosis and surgical management of dental root injuries suppose an extremely controversial question for dentist. Bearing in mind, that periapical cyst represents the most frequent injury in the maxilla, and that its differential diagnosis with chronic apical periodontitis shows a special complexity, decisions taken for its treatment acquires a major transcendence. the aim of this clinical case is to show clinical, radiographic Periapical Cyst diagnosis as long as its treatment by apicoectomy. Clinical and radiologic short-term outcome were favorable.